Investigation, remediation and protections of land resources - Genske, Dieter, D. (Whittles Publishing, 2007)
Annotation Genske addresses the fundamental science and engineering of land degradation and rehabilitation from a multi-disciplinary perspective. With a firm basis in soil science and allied subjects, this book provides a readable introduction for anyone in the area of land remediation, whether as a professional or as a student.
Keywords: Land use.; Land degradation.; Reclamation of land.; elektronické knihy; electronic books